Evaluation of modified passive haemagglutination assay for Vi antibody estimation in Salmonella typhi infections. Issue 8 (August 1992) - Kang, G; Sridharan, G; Jesudason, M V; John, T J
Abstract : A simple passive haemmagglutination assay (PHA) was developed to detect Vi antibodies, to improve the diagnosis of typhoid fever by small laboratories. The Vi capsular antigen of Salmonella typhi was extracted by alternate alcohol and acetone precipitation. Formalin fixed, sheep red blood cells treated with chromium chloride were sensitised with this Vi antigen and antibodies detected and measured by PHA. The test had a sensitivity of 83.3% among 30 cases of typhoid fever confirmed by culture. The specificity of the test was 94%, making it suitable for use in laboratories without facilities for IFAT or ELISA.